PENGARUH JENIS BAMBU, WAKTU KEMPA DAN PERLAKUAN PENDAHULUAN BILAH BAMBU TERHADAP SIFAT PAPAN BAMBU LAMINA - I.M. Sulastiningsih; Adi Santoso (BRIN Publishing, 2012)
The objectives of this study were to determine the effects of bamboo species, pressing time and pre-treatment of bamboo strips on the properties of laminated bamboo board (LBB). Bamboo strips for LBB fabrication were prepared from mature culms (± 4 years old) of andong bamboo (Gigantochloa pseudoarundinacea) and mayan bamboo (Gigantochloa robusta) collected from private gardens in West Java. The stript from each bamboo species were assigned into 3 groups iry pre-treatment methods, untreated, cold soaking in 7% boron solution for 2 hours, and bleached with 15% bydrogen perocide solution. The LBB was manufactured wring urca formaldeiryde (UF) added with wheat flour equal to 10% of UF. The cold pressing time applied were 4 hours and 5 hours. The results showed that the average density, moisture content and thickness swelling of laminated bamboo boards were 0.76 g) cum', 9.70% and 3.97% respectively. No delamination occurred in all samples using UF Jur, abich indicating high bonding quality. The average bonding strength (dry tests of laminated bamboo board made from andong was bigber (74.8 kg) cnl) than that of mayan bambou (67.9 kylen). Preservation and bleaching treatment of bamboo strips reduced the strength of 1.BB. Several properties of 1.BB were not significantly affected try bamino species esccept the compression strength. In general three-layer thick laminated bamboo board either made from andong or masan bambos hal strength values cumparable to wood strength clars 1. ubereas those stripe bleached witi 15% bydrogen perascide solution bad strength valuer similar to wood strength dair H. Laminated bamboo board is suitable for solid wood sulistitute and performs as alternative material for furniture, interior dezen and building materials.